An Empirical Study of Technical Debt Management as a Motivation for Forking - Njima, Mercy; Businge, John; Demeyer, Serge (In BENEVOL, 2020)
Forking is an often used idiom in software ecosystems that allows for the immediate reuse of existing software packages. Further, research shows that forking negatively impacts software quality since it distributes the maintenance effort across several repositories. However, there is a lack of sufficient knowledge exploring the validity and applicability of forking as an approach to solve software quality issues. In this position paper we present a plan to investigate the effectiveness of forking in managing technical debt.
Keywords: Forking; Software reuse; npm; SonarQube; Technical debt